ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMP N 1 GIRISUBO - Indriyaningsih Septeri, Dyah; Relaksa, Reli; Rahayu, Fitri; Diah Ayu Nuraini, Lutfita; Melinda, Dina (Mimbar Administrasi Mandiri, 2024)
The purpose of this study is to analyze the principal's leadership style in improving the performance of teachers in SMP Negeri 1 Girisubo. The research method used in this research is qualitative with a descriptive approach. Data collection was done through interviews, observation, and documentation. The interview process was conducted in-depth with several informants consisting of the principal and teachers in SMP Negeri 1 Girisubo. The selection of informants using purposive sampling technique with the following criteria: 1) Principal who served at least 3 years, 2) Teachers who teach at least 5 years at the school, and 3) Willing to be an informant. Interviews were conducted in a semi-structured manner with a pre-arranged interview guide beforehand. In addition, data were also collected through field observations to observe the principal's leadership style and teacher performance in the school environment. The results of this study show that the leadership style of the principal of SMP Negeri 1 Girisubo is democratic leadership. The leadership style of the principal of SMP N 1 Girisubo also has a very close relationship with teacher performance.